Cytopathological profile of patients with hepatic lesion: A hospital-based cross-sectional study from North-east India - Zothansangi,; Ralte, Wendy L; Sailo, Lalnunmawii; John Lalliandinga Tochhong,; Zohmingthanga, John; Anusuya, Ganesh Shanmugasundaram (Asian Journal of Medical Sciences, 2023)
Background: Cancer is not a notifiable disease in India. The data pertaining to liver cancer and hepatic lesions are very limited in India. Aims and Objectives: The current study was intended to observe the proportion of different types of liver lesions reported from private hospitals in Mizoram and also to study the association of liver malignancies in relation to gender and age. Materials and Methods: This is a cross-sectional study design. The data were collected from the cytopathology data base of a private laboratory (Genesis Laboratory) in Aizawl, Mizoram. Data regarding 204 patients with hepatic lesions, who have been referred from three private hospitals to a private laboratory in Mizoram from January 15, 2018, to November 31, 2021, were included in the study. Details regarding cytopathology reports of image-guided fine needle aspiration cytology of liver mass, age, and gender were collected. Air-dried smears received at a private laboratory were routinely stained with Leishman-Giemsa and Papanicolaou stains, Ziehl-Neelsen staining was done wherever needed. From the cytopathological diagnosis made, the frequency and patterns of various hepatic lesions were then analyzed using SPSS Version 22. Results: Out of 204 cases, 15 (7.35%) cases were reported as inadequate samples and 4 cases (1.96%) were inconclusive in diagnosis. Hence, remaining 185 study participants were included in the final analysis. The mean age was 58. Majority 122 (65.40%) were males and in the age group 41–60 years (49.19%). Majority of the lesions were malignant 145 (78.37%) and remaining 40 (21.62%) were benign lesions. The most common malignant lesion found was hepatocellular carcinoma (HCC) 87 (47.02%), followed by metastatic carcinoma 31 (16.75%). Liver malignancies were found to be higher among males (74.5%) as compared to females (14.3%), but were not statistically significant (P=0.08). The proportion of males (52.5%) versus females (36.5%) diagnosed with HCC was statistically significant (P=0.03). Conclusion: The most commonly reported liver malignancy was HCC. The proportion of males diagnosed with HCC was higher than females in the present study.